2016
DOI: 10.15244/pjoes/61853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Date Palm (Phoenix dactylifera) Seed Extract on Heavy Metals Concentrations in Carp (Cyprinus carpio)

Abstract: The effects of different doses of date palm (Phoenix dactylifera) seed (DPS) extract on heavy metals (Pb, Cd, As, Hg) concentrations of common carp (Cyprinus carpio) were evaluated. The fi sh (31.6±3.7 g) were assigned to fi ve treatments of three replications each. Five treatments were held using fi ve different DPS extracts at doses of 0% (control), 0.5%, 1%, 2%, and 4%. The results revealed that heavy metals concentrations of fi sh decreased in the 0.5% and 1% treatments (P<0.05). Hg and Cd concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Most research had concentrated on the use of date stones instead of powders as potential adsorbents. Some workers, 29 who fed different doses of date palm seed on some species of fresh water fish recorded a significant decrease on the heavy metal concentrations of the fishes. They therefore concluded that feeding common carp a diet enriched with date palm seed extract could decrease heavy metal concentration that can cause cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most research had concentrated on the use of date stones instead of powders as potential adsorbents. Some workers, 29 who fed different doses of date palm seed on some species of fresh water fish recorded a significant decrease on the heavy metal concentrations of the fishes. They therefore concluded that feeding common carp a diet enriched with date palm seed extract could decrease heavy metal concentration that can cause cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mohammadi et al . 19 , used date pits seeds for the removal of heavy metals including Pb, Cd, As, and Hg from Cyprinus carpio fish and results showed decreased concentrations of heavy metals inside the fish. Moreover, Al-Ghouti et al .…”
Section: Introductionmentioning
confidence: 99%
“…Date palm seeds are rich in fibers and phenolic compounds which mask the deteriorating effects of mercury. This useful function was recently pointed to in carp fish exposed to mercury and lead [ 47 ]. The supplementation of carp diet with date palm seeds at 1–4% of the diet significantly reduced muscle and liver content of mercury compared to positive control.…”
Section: Discussionmentioning
confidence: 99%